Adding fish meal into fermented moringa plus yellow corn in the diet does not affect performances but can recover breast yield of broiler - Zulfan Zulfan; Allaily Allaily; Fitrah Khairi; Sri Jeksi; Andreansyah Andreansyah; Indri Saputri (Universitas Sebelas Maret, 2024)
Objective: This study aimed to investigate the use of fermented domesticated-type Moringa oleifera leaves (FDMOL) + yellow corn (YC) + rice bran (RB) + top mix (TM) with the provision of fish meal (FM) in replacement of partial commercial diet (CD) to broiler performances and carcass yields.Methods: The study used 100 broiler chicks, unsex, MB 90 performed into Completely Randomized Design (CRD) consisting of 5 treatments and 4 replicates. The trial diets were: MCR= 84.5% CD + 5% FDMOL + 5% YC + 5% RB + 0.5% TM (moringa+), MCF= 84.5% CD + 5% FDMOL + 5% YC + 5% FM + 0.5% TM (moringa++), C1= 100% CD, C2= 84.5% CD + 7.5% YC + 7.5% RB + 0.5% TM, and C3 = 84.5% CD + 5% YC + 5% RB + 5% FM + 0.5% TM.Results: Better adding fish meal into the FDMOL + YC rather than no fish meal in replacement of partial commercial diet to feed on the broilers. Most parameter performances and yields seemed not affected on broilers fed the FDMOL + YC base replacement diet, but the breast tended to reduce, then adding FM into FDMOL + YC relatively recovered this valuable part of cuts-up similar to the control.Conclusion: Adding fish meal into fermented domesticated Moringa oleifera plus yellow corn in the diet did not affect performances but could recover the breast yield of broiler compared to those fed the moringa-based diet without adding fish meal.